Pengembangan Alat Tes Spinning Iron Untuk Latihan Kecepatan Pukulan Ukm Beladiri Upgri - Raka Adi Setya (YLPK Mahardhika, 2021)
Development of Spinning Iron Tool for Martial Arts Punch Speed ??Training. Faculty of Social Sciences and Sports Education. PGRI University in Semarang. 2021. This research is motivated by players who are less interested in participating in training, because the training system is too ordinary so that they feel bored and there is no multifunctional tool that can be used for martial arts. Therefore, the researcher aims to develop a spinning iron tool for training the speed of a martial arts stroke as a multifunctional training aid that can be used for martial arts training. This research is a research development or Research and Development (R&D). This research was conducted in several steps, namely: potential problems, data collection, product design, design validation, design revision, product testing, product revision, usage testing. The development of the spinning iron tool for martial arts stroke speed training was previously validated by material experts, media experts and 6 athletes for small-scale trials, 20 large-scale trial athletes. The subject of this research is the UKM martial arts, University of PGRI Semarang. Data collection techniques used in this study using an instrument in the form of a questionnaire. The data analysis technique of this research is descriptive qualitative and percentage descriptive quantitative. The results showed that the spinning iron tool was very suitable to be used as a game sports training aid. These results were obtained from the latest validation results of a) material expert at 87.5% or very feasible; b) media experts 95% or very feasible; c) field trial athletes of 90.2% or very feasible. Thus, the conclusion is that the spinning iron tool for martial arts stroke speed training has been declared very suitable for use as a martial arts training aid.